Marketing Intelligence System and its Impact in Determining Strategies of Competitive Positions - Azeez Hussein, Entisar (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The aim of the research is to know the impact of the marketing intelligence system adopted by the College as it is and the effectiveness of managing its marketing information and its ability to achieve a distinct strategic position in the Private university education market in Baghdad. In order to achieve these objectives, a model has been developed to determine the nature of the relationship and the impact between the system of marketing intelligence as an independent variable and the strategies of the competitive positions of the concerned faculty as a dependent variable. The research hypotheses have been formulated and tested using SPSS-22